The relative impact of public and private sector investment on economic and social development - Mohloare, Reabetswe (My University, 2019)
This paper empirically provides an analysis of the relative impact of public and private sector investment on economic growth and social development by using Ordinary Least Squares (OLS) and Generalized Method of Moments (GMM) estimations. The results firstly indicate that overall, public sector investment has relatively more impact on economic growth than private sector investment; with a significant positive relationship across the panel of 32 sub-Sahara African countries for the period 2005-2016. Secondly, when evaluating the relative impact of public and private sector investment on the social development variables (the value of education and health), the public sector investment is seen to positively contribute more than private sector investment. Thirdly, a mplementary relationship is found between the two sector investments in line with other studies that find that public sector investment is more productive for basic needs for development and this has a positive influence on private sector investment.